2016
DOI: 10.1088/1752-7163/10/4/046018
|View full text |Cite
|
Sign up to set email alerts
|

Aerobic exercise in polluted urban environments: effects on airway defense mechanisms in young healthy amateur runners

Abstract: In this study, the effects of aerobic exercise on the upper airways and their defense mechanisms were investigated in athletes. The athletes ran in two different environments: the downtown streets of the city of São Paulo (Street), more polluted, and an urban forest (Forest), less polluted. Thirty-eight young healthy athletes ran for 45 min d randomly during five consecutive days, with an interval of 48 h before changing environment. Clinical parameters and respiratory tract defense markers were evaluated befo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 35 publications
0
13
0
1
Order By: Relevance
“…Other studies assessed exhaled breath condensate (EBC) biomarkers. Two studies in runners reported unchanged EBC pH after exercise in clean or polluted air (47,53). In runners, concentration of interleukin (IL)-1β, IL-6, or IL-2 in EBC was unchanged relative to exposure to air pollutants (46), while another study reported decreased nitrate and increased malondialdehyde (MDA) concentrations, suggesting increased oxidative stress in the airways during exercise in highly polluted areas (29).…”
Section: Does Exercise In a Polluted Environment Affect Performance?mentioning
confidence: 99%
“…Other studies assessed exhaled breath condensate (EBC) biomarkers. Two studies in runners reported unchanged EBC pH after exercise in clean or polluted air (47,53). In runners, concentration of interleukin (IL)-1β, IL-6, or IL-2 in EBC was unchanged relative to exposure to air pollutants (46), while another study reported decreased nitrate and increased malondialdehyde (MDA) concentrations, suggesting increased oxidative stress in the airways during exercise in highly polluted areas (29).…”
Section: Does Exercise In a Polluted Environment Affect Performance?mentioning
confidence: 99%
“…17 Furthermore, 5 days of aerobic outdoor exercise significantly impaired nasal mucociliary clearance in the street runners group when compared with the forest runners group. 18 This suggests that regular outdoor exercise in AP can be potentially harmful to cardiorespiratory health.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
“…Mean results higher than Air pollution and exposure to certain substances are important factors that can influence airway acidity, and it is important to keep this in mind when analyzing EBC pH as a biomarker for various clinical conditions. Substances that have been proven to increase the level of hydrogen ions in exhaled breath-thus, lowering the pH value-include: O3 [73,74], SPM (suspended particulate matter) [73,75,76], black carbon [77], NO2 [76], benzene [76], ethylbenzene [76], TiO2 [78], PAH (polycyclic aromatic hydrocarbons) [79], wood dust [80], wood smoke [81], and cigarette smoke [82,83].…”
Section: Mechanical Ventilationmentioning
confidence: 99%